2013
DOI: 10.1016/j.juro.2013.02.3186
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship between National Institutes of Health Funding and Research Impact on Academic Urology?

Abstract: There is an association among the h-index, NIH funding and academic rank. The h-index is a reliable method of assessing the impact of scholarly contributions toward the discourse in academic urology. It may be used as an adjunct for evaluating the scholarly productivity of academic urologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 23 publications
2
62
0
Order By: Relevance
“…Colaco et al recently found a strong relationship between NIH funding, h index, and academic rank among academic urologists. 7 Additionally, Svider et al reported a similar relationship among funded and nonfunded academic otolaryngologists, noting that this objective bibliometric may have utility as an adjunct in the academic advancement process among faculty in either cohort. 37 Although these findings were similar to those in the current analysis, one interesting area of difference relates to the terminal degree an NIH-funded faculty member possesses.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Colaco et al recently found a strong relationship between NIH funding, h index, and academic rank among academic urologists. 7 Additionally, Svider et al reported a similar relationship among funded and nonfunded academic otolaryngologists, noting that this objective bibliometric may have utility as an adjunct in the academic advancement process among faculty in either cohort. 37 Although these findings were similar to those in the current analysis, one interesting area of difference relates to the terminal degree an NIH-funded faculty member possesses.…”
Section: Discussionmentioning
confidence: 92%
“…These issues and other potential limitations of the h index have been widely reported in the literature. 3,7,9,10,[12][13][14][15]18,23,25,26,[28][29][30]35,[39][40][41] Despite these known limitations, the h index is an objective measure that takes into account the frequency with which a faculty member has had an impact upon scholarly discourse within a field and has been shown in many analyses to have a strong association with academic promotion, receiving external funding, graduate medical education, and a variety of other factors measuring achievement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to date, little work has been done to determine metrics of faculty academic productivity within specific disciplines. At present, limited examinations focused mostly on publications and citations have been reported in subsets of physicians in relatively few specialties [18][19][20] [21,22] [23,24] [20,25] [ 20,26]. To date, no such examination has been done within the field of surgery.…”
Section: Introductionmentioning
confidence: 99%